Pemodelan Rain-On-Grid Untuk Kasus Banjir pada Polder Pluit, Jakarta - Riksa Nugraha Utama; Bobby Minola Ginting; Segel Ginting (Rekayasa Sipil, 2023)
Jakarta flood occurs almost every year, one of the reasons is the rapid development of its urban areas. Generally, Jakarta is categorized as a flat area, of which some locations are lower than the mean sea level, for example Pluit Polder area, thus being prone to flood. In this study, the rain-on-grid modeling with HEC-RAS software is carried out to determine the parts of the Pluit Polder that are still inundated so that better mitigation strategies can be achieved. The modeling results show that there are still inundated areas around the Pluit Polder ranging from 0.25 m to 2.75 m.